2013
DOI: 10.1021/jp401751z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surfactant on the Drying Patterns of Graphite Nanofluid Droplets

Abstract: We investigate the effect of surfactant on the formation of nanoparticle aggregates that resulted from evaporation of sessile nanofluid droplets theoretically and experimentally. A Monte Carlo model is developed to explain the transition from the coffee-ring pattern to the uniform deposition in drying the pinned sessile nanofluid droplets. The model applies the diffusion limited cluster-cluster aggregation approach coupled with the biased random walk of nanoparticles. The experiments show that the addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 35 publications
2
54
0
Order By: Relevance
“…[21][22][23][24][25][26][27] More specifically, Still et al 22 achieved a uniform deposition of colloidal particles on glass by adding Sodium dodecyl sulfate (SDS) to the drop dispersion.…”
Section: -12mentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25][26][27] More specifically, Still et al 22 achieved a uniform deposition of colloidal particles on glass by adding Sodium dodecyl sulfate (SDS) to the drop dispersion.…”
Section: -12mentioning
confidence: 99%
“…However, Crivoi and Duan 25,26 have shown that the formation of coffee ring of graphite nanoparticles is enhanced with the addition of Cetyltrimethyl Ammonium Bromide (CTAB)…”
Section: Sempels Et Almentioning
confidence: 99%
“…Among these patterns, the formation of "coffee ring" patterns is due to the "coffee ring" effect (explained in Section 2.4.1), the multi-ring patterns are related to the "stick-slip" motion of the contact line of the droplet during drying (mentioned in Section 2.3), the uniformdeposition patterns are the result of the inhibition of the "coffee ring" effect caused by the wide . Desiccation patterns of sessile drops of nanofluids: (a) "coffee ring" patterns in the suspension of single-walled carbon nanotube [57]; (b) multi-ring patterns in the suspension of titanium dioxide nanoparticles in ethanol [5]; (c) uniform-deposition patterns in the suspension of graphite nanoparticles [58]; (d) cracking patterns in the suspension of silica nanoparticles [43].…”
Section: Sessile Drops Of Nanofliudsmentioning
confidence: 99%
“…The particles get convected along with the fluid and deposited at the edge forming coffee ring pattern [15]. Pattern deposition depends on many factors like particle size [17,18], droplet size [18], nature of substrate surface [19,20], particle shapes [21,22], flow pattern inside droplet [15,23,24], presence of surfactant 15 and additives [25,26], substrate temperature [22], droplet composition [27] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Evaporation condition from the droplet surface affects the flow pattern leading to different deposition pattern [29,24]. For edge enhanced evaporation, fluid flows towards the center forming ring like deposits 25 and for center enhanced evaporation, fluid flows towards the top of the droplet leading to uniform deposits [24]. Internal flow generated inside the droplet by electrowetting can suppress the coffee ring forming uniform deposits [30].…”
Section: Introductionmentioning
confidence: 99%